ANALYSIS OF THE IMPACT OF ERP IMPLEMENTATION ON PROCESS OPTIMIZATION GLOBAL MARKETING AND SALES AT PT SINKONA INDONESIA LESTARI - Hersusetiyati Hersusetiyati; Rian Nanda Nugraha; Muhammad Algunadi; Bambang Susanto (PT. Altin Riset Publishing, 2025)
This research aims to analyze the implementation of the Enterprise Resource Planning (ERP) system at PT Sinkona Indonesia Lestari in the Marketing and International Sales unit. The implementation of ERP is expected to improve operational efficiency and provide better services to consumers, ultimately generating added value and maximizing benefits for all company stakeholders. This study employed a qualitative research method with an interactive qualitative approach. Data were collected through interviews, observations, and documentation studies. The results indicate that the ERP system implementation at PT Sinkona Indonesia Lestari has been running well. The ERP system helps in completing tasks, improving information quality, unifying the company's units, and optimizing operational performance. These findings are supported by interview data from key informants regarding ERP implementation, success factors, and employee adaptation to the ERP system. In conclusion, the implementation of ERP positively impacts the effectiveness and efficiency of the marketing and international sales unit's operations.